Flexible organic semiconductor thin films. Issue 33 (7th September 2015) - Gupta, Shiv K.; Jha, Purushottam; Singh, Ajay; Chehimi, Mohamed M.; Aswal, Dinesh K.
<x xml:space="preserve">Abstract</x> Research on organic semiconductor thin films has been accelerated due to their potential for low cost and large area flexible devices.